Upregulation of interleukin-19 in severe asthma: a potential saliva biomarker for asthma severity. Issue 3 (26th July 2021) - Saheb Sharif-Askari, Fatemeh; Saheb Sharif-Askari, Narjes; Goel, Swati; Mahboub, Bassam; Ansari, Abdul Wahid; Temsah, Mohamad-Hani; Zakri, Adel M.; Ratemi, Elaref; Hamoudi, Rifat; Hamid, Qutayba; Halwani, Rabih
Interleukin (IL)-19, a designated IL-20 subfamily cytokine, has been implicated in inflammatory disorders including rheumatoid arthritis, psoriasis and, lately, asthma. Here, through the analysis of transcriptomic datasets of lung tissue of large asthma cohorts, we report that IL-19 expression is upregulated in asthma and correlates with disease severity. The gene expression of IL-19 was significantly higher in lung tissue from patients with severe and mild/moderate asthma compared to healthy controls. IL-19 protein level, however, was significantly higher in the blood and saliva of patients with severe asthma compared to mild/moderate subgroups as measured by ELISA assay. IL-19 protein level was not affected by corticosteroid treatment in plasma. Our data provide insights into the potential use of IL-19 as a saliva marker for asthma severity and a potential therapeutic target. Plasma and saliva IL-19 are significantly upregulated in asthma and correlate with disease severity. Plasma IL-19 is not affected by steroid treatment. This suggests that IL-19 can be used as a biomarker of asthma severity. https://bit.ly/2QfYwpc